Teachers' lesson plan in the implementation of HOTS oriented physical education learning - Suhadi, Suhadi; Handoko, Riky Dwi; Mawarti, Sri; Santoso, Nurhadi; Antoni, Muhammad Sigit; Andriyani, Fitria Dwi (Jurnal Keolahragaan, 2023)
Lesson plan is the main key in learning. This study aims to analyze the lesson plans of High Order Thinking Skills (HOTS) oriented big ball games subject in physical education learning. This is descriptive quantitative research, with document analysis method. 16 lesson plans arranged by 16 teachers from 16 schools in Bantul Regency, Yogyakarta involved in this study. This study analyzes big ball game lesson plans including eight indicators: formulation of indicators, learning objectives, learning methods, learning media, learning materials, learning resources, learning activities, and learning assessments using document analysis guidelines with descriptors ranging from 1-5 scales (very good, good, acceptable, poor, very poor). The data analysis technique uses quantitative descriptive analysis and is presented in percentage. The results showed that the analysis of HOTS-oriented big ball game lesson plans as a whole was included in the sufficient category with a range of eight indicators 29-84. The learning resource component is the component of the lesson plan that has the lowest average of 1.94. The learning activity component is the lesson plan component that has the highest mean of 19.12. It can be concluded that learning resources need the main attention to be improved in order to realize HOTS learning. Therefore, future research should consider the type of game, level of education, region or area, and health conditions due to post-pandemic situations.